The Way Modeling Strategy Can Increase Activities and Abilities in Performing Obligatory Prayers in Students at SD Negeri 100620 Pasar Simundol - Nurmayani (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to determine the effectiveness of the Modeling the Way strategy in improving students' ability, engagement, confidence, and understanding in performing obligatory prayers at SD Negeri 100620 Pasar Simundol. This study was conducted on elementary school students to assess how the teacher's demonstration strategy, combined with students' active participation, influenced learning how to perform the correct prayer. This study used a mixed-method approach, including observation, interviews, documentation, and pre- and post-tests. The results showed that the Modeling the Way strategy significantly improved students' ability to perform physical movements and prayer readings correctly. Students showed increased accuracy in body position and pronunciation of Arabic phrases, especially in key readings such as takbir and Al-Fatiha. In addition to technical skills, this study revealed a marked increase in students' confidence and engagement during the lesson. Many students who were initially hesitant to participate became more willing to demonstrate their skills and take leadership roles in class activities. Furthermore, the strategy fostered a deeper understanding of the spiritual meaning of prayer, with students recognizing it as an act of devotion and connection with God, rather than simply a physical routine. The findings of this study indicate that *Modeling the Way* is an effective teaching strategy for enhancing the technical and spiritual aspects of religious education in elementary schools. The results highlight the importance of interactive, hands-on learning in teaching religious practices and suggest that regular practice, coupled with clear teacher demonstrations, can result in significant improvements in students’ skills and understanding. This study provides valuable insights into the potential of modeling as a tool to enhance religious education and support students’ spiritual growth.